Analysis of Transition Data by the Minimum-Chi-Square Method: An Application to Welfare Spells in Belgium - Cockx, Bart L. W. (The Review of Economics and Statistics, 1997)
In this paper we analyze transition data by means of the minimum-chi-square (MCS) method instead of the more commonly used maximum-likelihood (ML) method. The analysis includes exits to multiple destinations and unmeasured heterogeneity. In the empirical application, turnover in the welfare system in Belgium is found to be very high. Median duration is 4.5 months for men and 7 months for women, although these figures overstate turnover in that exits out of welfare include those occurring as a consequence of recipients moving to another municipality while remaining on welfare.